Channel estimation and IQ imbalance compensation for OFDM signal - Jing, Jiasheng (Nanyang Technological University, 2022)
In digital communication, a pilot is a known sequence in each signal frame. It is used for frame synchronization, as well as for channel estimation. Pilot design plays a key role in timing offset estimation and channel frequency response of the Orthogonal Frequency Division Multiplexing (OFDM) system. The designed pilot may consider the estimation of frequency selective/multipath channels, in-phase/quadrature-phase (IQ) imbalance together with other factors while providing accurate timing offset estimation/compensation and fulfilling signal. In this dissertation, an OFDM communication system model is established with noise, multipath fading and IQ imbalance to simulate the real wireless channel. I study and compare two classical channel estimation algorithms: the Least Square (LS) algorithm and the Minimum Mean Square Error (MMSE) algorithm. Then the influence of IQ imbalance on the performance of channel estimation algorithms is simulated. A special IQ imbalance estimation algorithm based on a new pilot pattern is proposed and simulated. Finally, this dissertation shows the performance of joint estimation, which proves that the proposed algorithm can effectively compensate for the non-ideality of the wireless channel and analog devices.